Unraveling the Correlation between Solvent Properties and Sulfur Redox Behavior in Lithium-Sulfur Batteries. Issue 16 (29th December 2018) - He, Qi; Gorlin, Yelena; Patel, Manu U. M.; Gasteiger, Hubert A.; Lu, Yi-Chun
Abstract : Systematic understanding of how solvent property influences Li-S redox chemistry is required to develop an effective electrolyte for Li-S batteries. In this study, we investigate the correlation between solvent property and Li-S redox chemistry in nine non-aqueous electrolyte solvents that cover a wide range of three main solvent physiochemical properties, namely dielectric constant (ɛ), Gutmann donor number (DN), and acceptor number (AN). We exploit various analytical techniques including cyclic voltammetry, rotating ring disk electrode technique, UV-Vis spectroscopy and galvanostatic measurement in a two-compartment cell. We show that the potential of S8 -reduction increases with increasing AN and that the polysulfide-reduction/oxidation is strongly influenced by the DN. The common discrepancy in the literature on the role of dielectric constant and donor number is addressed by examining the redox reactions, polysulfide stability, and the effect of salt concentration in acetonitrile - a solvent with high dielectric constant and low DN. We show that the DN is the primary descriptor for polysulfide redox reactions, as it controls the effective charge density of the solvated cation (Li + ), which affects the stability of polysulfides with different charge density via Pearson's Hard Soft Acid Base theory.